Influence of the soil's heterogeneity on the ground deformations above the heading of a shallow tunnel: centrifugal and numerical modeling (2011)
The current research work is focused on the ground deformations above a tunnel heading in heterogeneous soil. Physical and numerical modeling were undertaken in order to model the failure mechanisms of shallow tunnels in clays. Physical modeling was developed in the University of Los Andes geotechnical centrifuge machine and numerical modeling was conducted through the finite element method (FEM) using the CESAR program from the French Public Works Research Laboratory (LCPC).Soil model was composed by kaolinite and bentonite in three different portions, disposed in the centrifuge machine box container with the random fields theory in a two dimensional field. Soil variability was represented by the physical property of liquid limit, generating nine different combinations with the method of "Matrix decomposition technique". This method requires the determination and adoption of three statistical parameters such as the mean, standard deviation and correlation length of the liquid limit. For this purpose, typical clay from the Sabana Formation found in Bogota was used as the reference soil. Finally, a comparison is made between physical tests using heterogeneous soils and using an average value of liquid limit. Further analysis were performed to compare the surface and subsurface ground deformations between the three soils employed. Numerical analysis allowed to assess drained and undrained conditions in homogeneous models.